Children with chronic conditions in the school context: trends in brazilian scientific production - Goi, Cíntia Beatriz; do Nascimento , Francisco Junio; Siqueira, Fernanda Duarte; da Silva, Karem Azevedo; Benetti, Sabrina Azevedo Wagner; Arrué, Andrea Moreira; Neves, Eliane Tatsch (Disciplinarum Scientia | Saúde, 2024)
Objective: to identify and characterize trends in Brazilian scientific production in postgraduate programs regarding children with chronic conditions in the school context. Method: this is a narrative review of the literature in the Thesis and Dissertation Catalog of the Coordination for the Improvement of Higher Education Personnel, conducted between June and July 2022, using the combination of two strategies: children AND “chronic diseases” AND school* with 157 records, and children AND school* AND “special needs” with 170 records. National theses or dissertations concerning children with chronic conditions in the school context were included, regardless of the line of research or area of ​​knowledge. The selected studies were subjected to thematic content analysis. Results: 35 studies were included and the evidence was organized into three categories: limitations in the experience of children with chronic conditions in the school context, possibilities, and strategies. Conclusion: the trend in Brazilian scientific production regarding children with chronic conditions in the school context is recent. Emerging issues include difficulties in social interaction, school performance, and absence from school and possibilities such as the creation of bonds, implementation of teaching programs for child development, and strategies for improving professional training, government actions, and coordination between schools and health services.